Verging war between two atomic nations: Delineating coverage of India–Pakistan water dispute in global press - Mahmood, Tahir; C. Ogadimma, Emenyeonu; Raza, Syed Hassan; Yousaf, Muhammad; Khan, Sanan Waheed (SAGE Publications, 2024)
Arguably, journalistic practices should outline conflict reporting with a balanced approach to elicit non-violent responses. To date, no study has unfolded the coverage of the Indo-Pak potential war fueling “water dispute” by underpinning the theoretical notion of war and peace journalistic practices. Thus, drawing an analogy to war and peace journalism model, this article examines the media framing of the India–Pakistan water dispute in the USA, Chinese, Indian, and Pakistani newspapers. The study used a content analysis method to examine the use of framing techniques in newspapers. Findings supported that the global press' framing of the water dispute between India and Pakistan was dominated by war frames compared to peace frames. The Indian press used more war frames among the four countries while covering water disputes between rival nuclear neighbors. Moreover, it was found that the USA and Chinese press gave negligible coverage. The implications of the findings are discussed. © The Author(s) 2024.